Real-world comparison of different periprocedural antithrombotic strategies for atrial fibrillation catheter ablation. (14th October 2021) - Carvalho, R; Rodrigues, T; Rocha, R; Ribeiro, J; Silva, G.L; Carpinteiro, L; Cortez-Dias, N; Sousa, J
Abstract: Introduction: Atrial Fibrillation (AF) catheter ablation carries high bleeding and thromboembolic risks, requiring a detailed assessment of overall risk-benefit profile regarding antithrombotic strategy. Vitamin K Anticoagulant (VKA) and Non-Vitamin K Antagonist Oral Anticoagulant (NOAC) have been used in the latest years in this setting, and with different interruption protocols periprocedural. Our goal was to evaluate the rate of acute adverse events (AAE) and compare them according to antithrombotic strategy used periprocedural, in a real-world basis. Methods: A single-center retrospective study, including adult patients admitted to first AF catheter ablation, from 2004 to 2020. Different antithrombotic strategies (anticoagulation with VKA uninterrupted, anticoagulation with NOAC uninterrupted, no therapy or antiaggregation/interrupted ACO) were compared concerning the rate of any clinically relevant AAE; the composite of major AAE (hemopericardium and stroke/transient ischemic attack [TIA]) and minor AAE associated with vascular access. Descriptive statistics and logistic regression were used to compare groups according to the antithrombotic strategy with an alpha level of 0.05. Results: Among the 868 patients included (mean age 59±12 yo, 67, 5% [n=586] men), pulmonary vein isolation was performed under uninterrupted anticoagulation in 640 (73, 7%), of which 595 patients with NOAC (68, 5%) and 45 with VKA (5, 2%). AF was paroxysmal, persistent and long-standing persistent in 63, 4% (n=550), 21, 4% (n=185) and 15, 4% (n=133) patients, respectively. Mean CHADS-VASc score was 1, 86±1, 48. Over time there was a shift in the distribution of the type of antithrombotic therapy used, consistent with changes in recommendations (Graph 1). The composite outcome occurred in 6, 8% (n=62), including hemopericardium in 1, 8% (n=16), stroke/TIA in 0, 7% (n=6) and events related to vascular access in 1, 4% (n=13) [Table 1]. No anticoagulation therapy or antiaggregation/interrupted ACO was more associated to the outcome, driven by major AAE, although the difference did not meet statistical significance (p=0, 06) [Table 1]. No difference was found between VKA and NOAC group. Additionally, there was no diference in the incidence of hemorrhagic AAE since the implementation of an uninterrupted anticoagulation strategy periprocedural. Conclusion: In our population of patients submitted to AF catheter ablation, an uninterrupted anticoagulation strategy is associated with lower rate of AAE, either with VKA or NOAC. Our real-world results are reassuring of the benefit of an uninterrupted strategy, and consistent with recent controlled trials. Funding Acknowledgement: Type of funding sources: None.